2011
DOI: 10.1128/ec.00004-11
|View full text |Cite
|
Sign up to set email alerts
|

The F-Box Protein Fbp1 Regulates Sexual Reproduction and Virulence in Cryptococcus neoformans

Abstract: Cryptococcus neoformans is the leading cause of fungal meningitis in immunocomprised populations. Although extensive studies have been conducted on signal transduction pathways important for fungal sexual reproduction and virulence, how fungal virulence is regulated during infection is still not understood. In this study, we identified the F-box protein Fbp1, which contains a putative F-box domain and 12 leucine-rich repeats (LRR). Although fbp1 mutants showed normal growth and produced normal major virulence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
122
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(129 citation statements)
references
References 67 publications
6
122
1
Order By: Relevance
“…Our previous study has demonstrated that the expression of FBP1 was negatively regulated by glucose (21). Therefore, we checked the expression of Cck1 under glucose induction or repression conditions using qRT-PCR.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study has demonstrated that the expression of FBP1 was negatively regulated by glucose (21). Therefore, we checked the expression of Cck1 under glucose induction or repression conditions using qRT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Assays for melanin and capsule production were performed as previously described (21). In brief, melanin production was tested on niger seed agar and incubated at 30°C or 37°C for 2 days, and pigmentation of fungal colonies was assessed and photographed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations